AUDIT RESULTS OF COMPLINCE WITH THE UNIFIED CLINICAL PROTOCOL FOR RENDERING MEDICAL AID TO PATIENTS WITH ACUTE ISCHEMIC STROKE - Pariy, V.D.; Hryshchuk, S.M.; Korneychuk, N.M.; Harlinska, A.M.; Horokhova, L.V. (World of Medicine and Biology, 2019)
The problem of cerebrovascular diseases is one of the most urgent in modern medicine, in particular for the health care system of Ukraine, where the main cause of mortality is circulatory system diseases. Among them, ischemic stroke (IS) is particularly dangerous. The incidence in ІS is 270-280 cases per 100 thousand population and exceeds the average rate in the countries of the European Union (200 per 100 thousand population). In Ukraine, almost 100 thousand cases of primary IS are registered annually, 10-12% of them die from it, about 60% of them become disabled. According to the Institute for Measuring Health Indicators and Health Assessment (IHME), strokes in Ukraine are the second (after ischemic heart disease) causes of premature mortality and disability. In the general structure of the global disease burden in our country in 2017, the proportion of strokes was more than 8%.The purpose of the work was to carry out audit, determining compliance of the specialized medical care provision in stationary conditions to patients with acute ischemic stroke with the provisions of the branch clinical protocol on the example of Zhytomyr oblast health care institutions. The study was carried out by means of continuous sampling and retrospective medical cards analysis of inpatients diagnosed with ischemic stroke (MKH code -10 - І63.0-І63.9) who received inpatient care during an acute disease period in 26 health care facilities of Zhytomyr oblast in the first half of 2018. An audit of 508 treatment cases was conducted, which determined the compliance of performed diagnostic and therapeutic measures with the provisions of the "Unified clinical protocol for providing medical care for ischemic stroke" (Order of the Ministry of Health of Ukraine No. 602 dated 03.08.2012). The audit was conducted according to a specially developed "Audit Card", which included 21 indicators in 4 sections: diagnostics (5 indicators); medical treatment (11 indicators); rehabilitation (2 indicators); re-stroke prevention (3 indicators). The provisions of the unified clinical protocol for providing medical care for ischemic stroke regarding diagnosis and examination were fully observed in 25.0 ± 1.9% of cases, regarding medicine prescription - while treatment to only 7.9 ± 1.2% of patients. Insufficient use of the protocol provisions regarding patient rehabilitation was observed - early mobilization during the acute ischemic stroke was carried out in 59.8 ± 2.2% of cases, an individual rehabilitation plan was available in 54.7 ± 2.2% of treatment cases. Measures aimed at preventing re-stroke complied with the protocol in 59.8 ± 2.2% of cases. High frequency of prescribing medicine of neuroprotective and nootropic groups with unproved efficiency was observed (81.9% of cases). Complete compliance with 21 indicators of the protocol was observed in treatment of only 15 patients (3.0 ± 0.8% of cases). Compared with the results of the preliminary audit conducted in 2014, there has been a markedly positive dynamics in the neuroimaging (the proportion of the surveyed increased from 26.2% to 50.2%), the prescription of anti-aggregators (increased from 70.1% to 87.0%). Despite the availability of current healthcare guidelines for rendering medical aid to patients with acute ischemic stroke, which have been introduced since 2012, we discovered that they were fully complied with for the treatment of only 3.0% of patients. This is conditioned by insufficient diagnosis verification, prescription of medication with undetectable efficiency, lack of modern approaches to rehabilitation of patients and the prevention of recurrent strokes.
Keywords: audit; ischemic stroke; protocol; indicator; medical aid